(untitled) (Journal of Engineering, 2024)
Reactive Powder Concrete (RPC) is a type of high-performance concrete that is known for its exceptional strength and durability also RPC is one of the new composite materials that allow for the most efficient use of materials, which benefits the concrete industry economically. Additionally, it improves environmental sensitivity. The main objective of this paper is the determine some characteristics of RPC, such as (compressive strength and fresh density) after exposure to different curing temperatures (60, 120, and 200) oC for 4 hours due two days. This study involves many variables such as micro steel fibers content with 1% by vol. of reactive powder concrete samples as well as elevated temperature. It was discovered that the optimum temperature that was used after conducting the tests was 60 Celsius, as it gave the best results for the mechanical properties of RPC, which were adopted in the rest of the tests. The value of fresh density increased by about (1.95%) and compressive strength increased by about (33.3%) at 60 oC for the age of 28 days in contrast to the reference mixture.